2013
DOI: 10.2139/ssrn.2279355
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Microinsurance Demand

Abstract: The purpose of this article is to structure the extant knowledge on the determinants of microinsurance demand and to discuss unresolved questions that deserve future research. To achieve this outcome, we review the academic literature on microinsurance demand published between 2000 and early 2013. The review identifies 12 key factors affecting microinsurance demand: price, wealth, risk aversion, non-performance risk, trust and peer effects, religion, financial literacy, informal risk sharing, quality of servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…In general, although the literature on microinsurance is extensive and covers many locations, the available data remain limited, given the relatively young programs and the challenges of collecting data in emerging economies. As Eling, Pradhan, and Schmit () mention in their literature review, a pattern across the literature is that location‐specific qualities seem relevant. Until we can obtain better data over numerous locations and systems, our ability to make general statements is limited.…”
Section: Adverse Selection: Theory and Empiricsmentioning
confidence: 98%
“…In general, although the literature on microinsurance is extensive and covers many locations, the available data remain limited, given the relatively young programs and the challenges of collecting data in emerging economies. As Eling, Pradhan, and Schmit () mention in their literature review, a pattern across the literature is that location‐specific qualities seem relevant. Until we can obtain better data over numerous locations and systems, our ability to make general statements is limited.…”
Section: Adverse Selection: Theory and Empiricsmentioning
confidence: 98%
“…The research focuses on microinsurance demand and program design. Eling et al (2014) summarize 12 potential determinants of microinsurance demand in Outreville's insurance demand framework. However, the discussion on the demand for microinsurance is inconclusive.…”
Section: Risk Identificationmentioning
confidence: 99%
“…This paper finds that quality and prices show a positive effect on competitive advantage for these companies in Jordan. (Eling, 2013) studies the determinants of micro-insurance demand. This paper identifies 12 key factors affecting micro-insurance demand, and further highlights that research focused on the role of contract performance (including basis risk and quality), trust, financial literacy and informal risk-sharing mechanisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8, No. 5;2016 In the Table 4 appear the multiple regressions for the impact of the cost of insurance, discrimination and credit score on competitiveness between insurance companies. As indicated from table above, we found that there is a positive significant relationship between the costs of insurance on competitiveness.…”
Section: Wwwccsenetorg/ijefmentioning
confidence: 99%